2016
DOI: 10.5539/elt.v9n3p174
|View full text |Cite
|
Sign up to set email alerts
|

How School Leaders Might Promote Higher Levels of Collective Teacher Efficacy at the Level of School and Team

Abstract: Leaders search for effective leadership practices to ensure success. A quantitative study was conducted to determine what behaviors a leader could use to improve collective teacher efficacy at the level of the entire faculty and at the level of grade level teams. This article focuses on using the inverse relationship between transformational leadership and collective teacher efficacy to strengthen efficacy of teachers of English Language Learners. The Collective Efficacy Scale (Goddard, 2001) was modified to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…The third approach involves telling stories of past successes to remind individual teachers or teams of their abilities. The final approach to improving collective teacher efficacy is through affective states, which entail fostering excitement and pleasure in the accomplishments or tasks being pursued (Goddard et al , 2004; Prelli, 2016).…”
Section: Collective Teacher Efficacymentioning
confidence: 99%
“…The third approach involves telling stories of past successes to remind individual teachers or teams of their abilities. The final approach to improving collective teacher efficacy is through affective states, which entail fostering excitement and pleasure in the accomplishments or tasks being pursued (Goddard et al , 2004; Prelli, 2016).…”
Section: Collective Teacher Efficacymentioning
confidence: 99%
“…Conversely, Prelli (2016) found a negative relationship between transformational leadership and CTE. Additionally, in a few studies of organizations outside of education, authentic leadership was positively correlated with collective efficacy (Xiong & Fang, 2014), as were transactional and transformational leadership (Sudha, Shahnawaz, & Farhat, 2016), whereas laissez-faire leadership was negatively correlated with collective efficacy (Sudha et al, 2016).…”
Section: Principal Leadership and Efficacymentioning
confidence: 82%
“…In an attempt to more clearly understand how the construct of leadership relates to both teacher efficacy and CTE, the researcher considered the leadership of principals (inclusive of instructional, transformational, transactional, authentic, and laissez-faire), teachers, and a few types of leaders outside of education. Literature is still emerging in these areas, and several studies have indicated that leadership positively and significantly correlates with efficacy beliefs (R. Goddard et al, 2015;Hallinger, Hosseingholizadeh, Hashemi, & Kouhsari, 2017;Ninković & Knežević Florić, 2018;Ross & Gray, 2006); however, the findings have been somewhat mixed in regard to principal leadership (Fancera & Bliss, 2011;Prelli, 2016). Findings have been more conclusive in the area of teacher leadership, showing more consistent, strong connections to CTE in the literature (Angelle et al, 2011;Angelle & Teague, 2014;Derrington & Angelle, 2013).…”
Section: Leadership and Efficacy Beliefsmentioning
confidence: 99%
“…, 2015). In climates where collective responsibility, continued learning and collaboration are facilitated, CTE exists (Prelli, 2016). Despite what is known, research focused on how to establish or enhance CTE within schools has yet to be extensively explored (Mosoge et al.…”
mentioning
confidence: 99%